THE RELATIONS OF RELIGION AND ETHNICITY OF URBAN COMMUNITIES IN SURABAYA - Basyir, Kunawi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: The phenomenon of social life related to religion and ethnicity of urban communities in Surabaya has been and is becoming a special concern for the government of Surabaya and academicians Because, the metropolitan city (Surabaya) which has various types of differences in religion, ethnicity, and culture of ethnic communities (Javanese, Madurese, Chinese, Arabic) has provided its color of in-depth study and research. This article will describe the results of studies and research with the title "religious relations and ethnicity of urban communities in Surabaya" deeply and in detail. This study used a qualitative method, where data collection is held by participant observation and open interviews, then analyzed the data using the social construction theory approach. This research found that religion is no longer a binding tool (unifier) for various ethnic and cultural backgrounds. On the contrary, religion is thought to have been a trigger for the emergence and development of the inter-ethnic conflict.Keywords: religion, ethnicity, social conditions, urban society